2012
DOI: 10.1371/journal.pntd.0001758
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Circulating Cathodic Antigen (CCA) Urine-Tests for Diagnosis of Schistosoma mansoni Infection in Cameroon

Abstract: BackgroundThe Kato-Katz is the most common diagnostic method for Schistosoma mansoni infection. However, the day-to-day variability in host egg-excretion and its low detection sensitivity are major limits for its use in low transmission zones and after widespread chemotherapy. We evaluated the accuracy of circulating cathodic antigen (CCA) urine-assay as a diagnostic tool of S. mansoni. In comparison, a low sensitive CCA test (CCA-L) was assessed.MethodologyThe study was conducted in three settings: two foci w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 23 publications
7
78
1
Order By: Relevance
“…This point-of-care urine CCA assay has been used in community studies to estimate the prevalence of schistosomiasis (177) and for successful assessments of PZQ treatment (177,183). Overall, compared to the KK test, this assay is a convenient and efficient method for screening and mapping schistosomiasis cases in communities with medium to high levels of endemicity (177,(183)(184)(185). However, day-to-day fluctuations in urine CCA dipstick test results have been observed, which has led to the suggestion that more than one urine sample collected on different days may be required for more accurate diagnosis.…”
Section: Antigen Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point-of-care urine CCA assay has been used in community studies to estimate the prevalence of schistosomiasis (177) and for successful assessments of PZQ treatment (177,183). Overall, compared to the KK test, this assay is a convenient and efficient method for screening and mapping schistosomiasis cases in communities with medium to high levels of endemicity (177,(183)(184)(185). However, day-to-day fluctuations in urine CCA dipstick test results have been observed, which has led to the suggestion that more than one urine sample collected on different days may be required for more accurate diagnosis.…”
Section: Antigen Detectionmentioning
confidence: 99%
“…However, day-to-day fluctuations in urine CCA dipstick test results have been observed, which has led to the suggestion that more than one urine sample collected on different days may be required for more accurate diagnosis. Also, it has been shown that the sensitivity of the CCA assay for diagnosing S. mansoni infection is reduced in areas of low endemicity and that CCA positivity is correlated strongly with infection intensity (178,184,186). Nevertheless, a recent study of patients from different areas in Uganda where S. mansoni is endemic reported that a single urine CCA assay had increased diagnostic accuracy compared to multiple KK tests and that the test sensitivity correlated with infection prevalence (187).…”
Section: Antigen Detectionmentioning
confidence: 99%
“…Compared with microscopy, urine reagent strips used to detect microhaematuria or proteinuria as a proxy for S. haematobium infection are cheap, quick, and easy to use (Mott 1985; Brooker 2009); have no technical requirements; and are less influenced by the circadian production of schistosome eggs (Murare 1987; Lengeler 1991b). Furthermore, some studies have shown that the sensitivity of these strips is higher than that of urine filtration (French 2007; Robinson 2009), and that a single test with microhaematuria strips is more sensitive than a single test with urine filtration (Taylor 1990)—features that make these strips suitable for screening of urogenital schistosomiasis in the field. However, results should be interpreted against the background of risk for schistosomiasis, as well as any other signs and symptoms that could be indicative of other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The POC-CCA assay is commercially available through Rapid Medical Diagnostics (Pretoria, South Africa), and has been evaluated for sensitivity, specificity, and ease of use in a number of settings. [14][15][16][17][18][19] However, there has been concern that the cost of the POC-CCA assay may be a barrier to widespread adoption of this technique for schistosomiasis control programs 14,16,17,20 ; therefore, there is a need for a comprehensive evaluation of the cost-effectiveness of the POC-CCA technique in relation to other available tests. 13 Although the cost of the materials and equipment are commonly cited as expenses, other cost contributions such as labor and transportation are rarely discussed.…”
Section: Introductionmentioning
confidence: 99%